A new leaf blight disease of turfgrasses caused by Microdochium poae, sp. nov. (4th March 2019) - Liang, Junmin; Li, Guangshuo; Zhao, Meiqi; Cai, Lei
ABSTRACT: A novel species of Microdochium was identified as the causal agent of a leaf blight of Poa pratensis (Kentucky blue grass) and Agrostis stolonifera (Creeping bentgrasses), two cold-season turfgrasses widely grown on golf courses in northern China. This disease first appears as small, water-soaked, and scattered leaf spots. Under conditions of high temperatures and successive days of rain, the infected leaves rapidly lose their integrity and large diseased patches appear. Fungal strains were isolated from blighted leaf spots. A phylogenetic analysis based on the nuc rDNA internal transcribed spacer regions and 5.8S rRNA gene (ITS1-5.8S-ITS2 = ITS) and parts of the β-tubulin ( TUB2 ) and RNA polymerase II second largest subunit ( RPB2 ) genes strongly supported that these isolates are a distinct evolutionary lineage in Microdochium (Microdochiaceae, Xylariales) that represents a new taxonomic species, herein named as M. poae . Microscopic characters confirmed that these strains were morphologically distinct from known Microdochium species. The pathogenicity of M. poae was confirmed by inoculating spore suspension on both grasses and reisolation of the pathogen from symptomatic tissues. The optimal growth temperature suggests that the occurrence of the new leaf blight disease caused by M. poae was significantly different from the microdochium patch disease caused by M. nivale .